2013
DOI: 10.4318/tjg.2013.0511
|View full text |Cite
|
Sign up to set email alerts
|

Major predictors for difficult common bile duct stone

Abstract: Girifl ve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 10 publications
4
21
0
1
Order By: Relevance
“…[12] In our study, we did not find an association between stone size and the failure to clear the biliary system on the index ERCP; again, this could be due to the fact that only a small proportion had large CBD stones in our cohort (9.6% had a stone larger than 15 mm) as well as the fact that endoscopists could have utilized advanced endoscopic techniques to clear these stones during the index ERCP. The presence of a stricture below a stone is an intuitive cause for increased difficulty in extracting a stone, which was the case in our study and is consistent with the literature[18] where a stemware-shaped CBD was associated with a bile duct clearance rate on the index procedure of only 41.2%; even in those with stones less than 1 cm in size, the clearance rate on the index procedure was only 62.5% while the overall procedure-related adverse events were relatively high, that is, 14.7%. [11] In addition, the presence of an angulation in the distal CBD has been thought to be a cause of decreased clearing rates of the biliary system[4] but was not the case in our cohort.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[12] In our study, we did not find an association between stone size and the failure to clear the biliary system on the index ERCP; again, this could be due to the fact that only a small proportion had large CBD stones in our cohort (9.6% had a stone larger than 15 mm) as well as the fact that endoscopists could have utilized advanced endoscopic techniques to clear these stones during the index ERCP. The presence of a stricture below a stone is an intuitive cause for increased difficulty in extracting a stone, which was the case in our study and is consistent with the literature[18] where a stemware-shaped CBD was associated with a bile duct clearance rate on the index procedure of only 41.2%; even in those with stones less than 1 cm in size, the clearance rate on the index procedure was only 62.5% while the overall procedure-related adverse events were relatively high, that is, 14.7%. [11] In addition, the presence of an angulation in the distal CBD has been thought to be a cause of decreased clearing rates of the biliary system[4] but was not the case in our cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Although stone characteristics like the number or size and relation to the CBD diameter were not found to be associated with the stone clearance rates in studies,[12] this is in contrast to others[11151718] where larger stones (≥17.7 ± 6 mm) were found to require a combination of advanced ERCP techniques to achieve duct clearance. [12] In our study, we did not find an association between stone size and the failure to clear the biliary system on the index ERCP; again, this could be due to the fact that only a small proportion had large CBD stones in our cohort (9.6% had a stone larger than 15 mm) as well as the fact that endoscopists could have utilized advanced endoscopic techniques to clear these stones during the index ERCP.…”
Section: Discussionmentioning
confidence: 70%
“…However, existence of periampullary diverticula did not show any association with difficult stones. There are reports that support our findings while there are others that suggest the opposite [2, 6, 7, 9]. Probably these diversions are due to differences in ERCP experience of the reporting centers.…”
Section: Discussionsupporting
confidence: 73%
“…Recent literature has reported that difficult stones can be seen in 7–20% of patients while in our study we have similarly experienced difficult stones in 13.6% of patients, and additional interventions were indicated [3, 69]. We have observed that general features of the patients with difficult stones are similar to the recent literature, such as older age, dilation of the CBD, impaction of the stone, stricture distal to the stone, and opening anomaly of the papilla [1, 6, 9]. Additionally, it must be noted that patients with difficult stones had higher bilirubin levels, while they had relatively lower hepatic enzyme levels.…”
Section: Discussionsupporting
confidence: 62%
“…The introduction into clinical practice of baskets of various sizes and configurations (3)(4)(5), various lithotripsy methods (6,7) considerably increased the possibilities and the safety of their endoscopic debridement. Sufficient clinical material made it possible to significantly improve the "tactics of X-ray endoscopic treatment of choledocholithiasis" (8,9), assessing its potential (10,11). Despite this, there are still clinical observations when it is necessary to perform an open laparotomy with choledocholithotomy sometimes against the background of not only high obstructive jaundice, but also purulent cholangitis, which does not always end in the patient's recovery (12,13).…”
Section: Introductionmentioning
confidence: 99%